Long-term contact-coupled wear prediction for metal-on-metal total hip joint replacement - Harun, Mokhtar N. (Professional Engineering Publishing Ltd., 2009)
The major long-term failure identified for metal-on-UHMWPE is aseptic loosening due to wear generation. Metal-on-metal hip joint replacement has been found to have minimal wear compared to metal-on-UHMWPE. The objective of this study was to apply the computational simulation in predicting wear of metal-on-metal total hip joint replacement. Finite-element model of half ball and the 45° inclined cup was developed to represent the femoral head and acetabular cup, respectively. A simple Archard's equation was used to simulate the wear process combining with the finite-element model. The wear simulation of 28 mm femoral head with 60 µm diametral clearance was carried out for up to 50 million cycles, and subsequently analysed. The contact pressure decreased dramatically from the initial cycle to the first million cycles accompanied by an increase of contact area; however, the decrease of contact pressure was very small between 30 and 50 million cycles. There was relatively good agreement in volumetric wear between the present and hip simulator study. The total predicted volumetric wear for 50 million cycles was 4.2 mm3. It was found that the post-wear bearing surface would be advantageous to the hip implant by increasing the lubricating film and thus decreasing wear.